1984
DOI: 10.1172/jci111466
|View full text |Cite
|
Sign up to set email alerts
|

Isozymic changes in myosin of human atrial myocardium induced by overload. Immunohistochemical study using monoclonal antibodies.

Abstract: Abstract. An immunohistochemical study using monoclonal antibodies specific for the heavy chains ofeither human atrial (HCa) or ventricular (HC(#) myosin was performed to clarify the distribution of each isozyme in normal as well as pressure-overloaded human hearts. In normal human ventricles, all muscle fibers were stained by a monoclonal antibody (HMC14) specific for HC(, whereas a small number of fibers reacted with a monoclonal antibody (CMA19) specific for HCa. In contrast, in normal human atria, almost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
3

Year Published

1987
1987
2002
2002

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 15 publications
4
28
1
3
Order By: Relevance
“…We reported the isozymic redistribution in human atria by pressure overload, that is, HCa, a predominant myosin isozyme in the atrium was replaced by lI in atria subjected to pressure overload. The extent of isozymic change correlated well with atrial pressure (10). Here, we observed a similar increment of (2 in pressure-overloaded atria.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…We reported the isozymic redistribution in human atria by pressure overload, that is, HCa, a predominant myosin isozyme in the atrium was replaced by lI in atria subjected to pressure overload. The extent of isozymic change correlated well with atrial pressure (10). Here, we observed a similar increment of (2 in pressure-overloaded atria.…”
Section: Resultssupporting
confidence: 85%
“…In a previous report, we showed that a redistribution of isozymes from HCa to HCB (,B) can occur by pressure overload even in the human atrial myocardium (10). In this study, we examined whether #2 showed a change similar to #I by pressure overload.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations